The Main Character in ‘Lowlife’ Music Video by Neck Deep Band : A Semiotic Approach - Ida Ayu Leony Pratiwi; I Nengah Sudipa; Anak Agung Sagung Shanti Sari Dewi (Humanitatis : Journal of Language and Literature, 2022)
In social life, the study of semiotic is used to uncover the meaning implied in signs. Depart from that, the study study that is entitled “The Main Character in ‘Lowlife’ Music Video by Neck Deep Band: A Semiotic Approach” discusses the meaning conveyed from the main character in the music video. The main character was chosen as the object of research because it plays an important and most influential role in the conflict from the beginning to the end of the music video. The study is aimed to identify the visual elements contained in the main character of the music video from Neck Deep Band entitled “Lowlife”. The second aim is to analyze the denotative and connotative meaning conveyed from the main character in the music video clip.The data was collected through documentation method and note taking technique.The collected data was analyzed using descriptive qualitative method, and was based on the theory of visual communication proposed by Dyer (1993)`and the theory of denotative and connotative meaning proposed by Barthes (1957). The result of the study shows that the main character Jett contains the five visual communication elements, namely : Appearance, Manner, Activities, Props and Settings, and also Image. Jett represents a form of a cynical expression to majority elite social class that living in boring life with stiff demeanor who see themselves above anything else.